Knowledge is the most powerful tool in the fight against tuberculosis - Miroslav Ilic; Dragan Bjelic; Jovan Javorac; Kristina Tot Veres; Dejan Zivanovic; Dragica Kovačevic; Nikola Maric; Nensi Lalic; Nikola Colic; Mihailo Stjepanovic (Journal of Infection in Developing Countries)
Introduction: In October 2022, after almost two years, tuberculosis reclaimed its first place as the world's deadliest infectious disease, replacing COVID-19. Since knowledge is the most powerful tool to combat any disease, the primary goal of our study was to assess patients' knowledge of tuberculosis and its relationship to their socio-demographic status.